Amlodipine induced Gingival Overgrowth - Aryal, Deepa; Shahi, Kripa; Shrestha, Surendra Man (Journal of Nepalese Society of Periodontology and Oral Implantology, 2018)
Gingival overgrowth caused by drug is a well-documented unwanted side effect and mostly caused by Nifedipine. Newer generation calcium channel blocker, amlodipine, has been used with the increasing frequency to overcome the adverse effect of first and second generation dihydropyridine derivatives of Calcium Chanel Blocker. The pathogenesis of gingival enlargement is uncertain and the treatment is still largely limited to the maintenance of an improved level of oral hygiene and surgical removal of the overgrowth tissue. This article reports the amlodipine induced gingival enlargement and its treatment in a 60 years old hypertensive female patient.